PROFESSIONALLY-APLIED PHYSICAL PREPARATION OF A STUDENT - A. D. Jurbina; V. V. Antipas; V. V. Gryaznova (Научный вестник МГТУ ГА, 2014)
Questions of professionally-aplied physical preparation of specialists of civil aviation. Standarts on the fitness of the MSTU CA students have been determined. Qualification characteristics of motor quality have been developed depending on the students’ speciality.